2022
DOI: 10.3390/cli10090128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ECMWF-SEAS5 Seasonal Temperature and Precipitation Predictions over South America

Abstract: Nowadays, a challenge in Climate Science is the seasonal forecast and knowledge of the model’s performance in different regions. The challenge in South America reflects its huge territory; some models present a good performance, and others do not. Nevertheless, reliable seasonal climate forecasts can benefit numerous decision-making processes related to agriculture, energy generation, and extreme events mitigation. Thus, given the few works assessing the ECMWF-SEAS5 performance in South America, this study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Because of these systematic biases, forecast skill is generally improved by linear bias correction, as also found in previous studies (e.g., Charles et al, 2013;Crochemore et al, 2016;Ferreira et al, 2022). The exception is the wet season of dry years, where bias correction could be detrimental because it increases the forecasted precipitation away from the observations (see Figure 9).…”
Section: The Skill Of Seasonal Precipitation Forecasts In South Koreasupporting
confidence: 73%
See 2 more Smart Citations
“…Because of these systematic biases, forecast skill is generally improved by linear bias correction, as also found in previous studies (e.g., Charles et al, 2013;Crochemore et al, 2016;Ferreira et al, 2022). The exception is the wet season of dry years, where bias correction could be detrimental because it increases the forecasted precipitation away from the observations (see Figure 9).…”
Section: The Skill Of Seasonal Precipitation Forecasts In South Koreasupporting
confidence: 73%
“…Although SPFs provide skilful forecast over the climatology during the wet season of dry years, we found that the limitation lies in anticipating dry years. A previous study also investigated to show if SPFs from ECMWF have the potential to predict extreme dry conditions over South America (Ferreira et al, 2022), and found that this potential is shown mainly in the tropical sectors having strong connection with ENSO (e.g., Weisheimer & Palmer, 2014; Shirvani & Landman, 2015 for Iran). Our result also shows that both SPFs and ENSO failed to capture a reliable signal of a dry year in South Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even with a wetter simulation pattern, these models underestimate rainfall The ensemble mean maintains the warmer behavior of the models in sectors such as the Andean region and north-central Argentina, as well as the colder pattern in extreme southern Argentina and northern SA. Other studies have also found a colder bias of climate models in SA [27,[102][103][104][105][106] due to the limitation of the models in simulating the complex topography of the continent, especially over regions such as the Andes and the La Plata Basin [107], as well as the initial soil moisture conditions since this variable modifies the surface temperature amplitude [108].…”
Section: Resultsmentioning
confidence: 99%
“…Enhancing forecast skill begins with understanding the sources and limits of S2S predictability within the Earth system. Previous studies revealed that there are potential sources of predictability for the S2S timescales, including the MJO, the state of ENSO, soil moisture, snow cover and sea ice, stratosphere–troposphere interaction, and tropical–extratropical teleconnections (e.g., Ferreira et al, 2022; Ichikawa & Inatsu, 2017; Kim et al, 2014; Mariotti et al, 2020; Wang et al, 2016). The sources of S2S predictability are each briefly discussed as follows:…”
Section: Sources Of S2s Predictability Within the Context Of The Sout...mentioning
confidence: 99%